2015
DOI: 10.1589/jpts.27.1435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-week healthy-life exercise program on oxidized low-density lipoprotein cholesterol and carotid intima-media thickness in obese elderly women

Abstract: [Purpose] This study examined the effects of a 12-week exercise program on plasma level of oxidized low-density lipoprotein cholesterol in obese elderly women, who are at increased risk of heart disease morbidity. [Subjects and Methods] Twenty participants were assigned into either a control (n = 10) or a supervised exercise program (n = 10) group. The 12-week exercise intervention was performed 3 days per week and involved combined aerobic exercise, resistance exercise, and traditional Korean dance. [Results]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…CIMT was measured using B-mode ultrasound and a 10-MHz probe (LOGIQ 3, GE Healthcare, Wauwatosa, WI, USA). During measurement of the carotid arteries, the subjects lay on their backs in a dark room, turned their heads 45 degrees, and fully exposed the carotid arteries after they relaxed for minimum 10 minutes; left carotid artery was then measured by ultrasound 21 , 22 ) . Three IMT measurements of diastolic images on each side at 10 mm before or after the carotid bifurcation were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…CIMT was measured using B-mode ultrasound and a 10-MHz probe (LOGIQ 3, GE Healthcare, Wauwatosa, WI, USA). During measurement of the carotid arteries, the subjects lay on their backs in a dark room, turned their heads 45 degrees, and fully exposed the carotid arteries after they relaxed for minimum 10 minutes; left carotid artery was then measured by ultrasound 21 , 22 ) . Three IMT measurements of diastolic images on each side at 10 mm before or after the carotid bifurcation were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…A 12-week healthy-life exercise program was reported to reduce circulating ox-LDL levels and carotid IMT in obese elderly women. 44 Tavridou et al 45 reported that treatment with simvastatin 40 mg/d for 12 weeks significantly reduced circulating ox-LDL levels by 6.5% ± 5.2% and 31.1% ± 5.0% in hypercholesterolemia subjects with and without CHD, respectively. Likewise, a study by Aydin et al 46 showed that both rosuvastatin 20 mg/d and atorvastatin 80 mg/d had comparable effects on circulating ox-LDL levels.…”
Section: Effect Of Medical Therapy and Lifestyle Modifications On Ox-mentioning
confidence: 99%
“…Studies in adults have shown reductions in plasma markers of oxidative stress after weight loss induced by a lifestyle intervention [22,23]. A few studies have evaluated the effect of weight loss programs on ox-LDL lipoproteins [15,24,25], anti ox-LDL and PON1 [26] in obese pediatric populations.…”
Section: Discussionmentioning
confidence: 99%